Dominant Discourses About What It Means to Be “Good” at Mathematics: How High-Achieving Young Women Negotiate Tensions Within Their Evolving STEM Identities - Terrie Galanti; Nancy Holincheck (Education Sciences)
Cultural beliefs about what it means to be “good” at mathematics profoundly impact students’ perceptions of their abilities and how they come to see themselves in STEM. These beliefs can be traced back to dominant societal discourses about mathematical aptitude and achievement. These dominant discourses are communicated to students in a myriad of ways through family, friends, media, and overall societal norms. They reify deficit perspectives (often gendered, classed, and racialized) about who is or can be mathematically competent. In this investigation, we used a framework of dichotomies within dominant discourses about what it means to be “good” at mathematics to interpret retrospective narratives from a larger phenomenological study of accelerated mathematics course-taking. Focus group and individual interview data from two high-achieving young women were analyzed to understand how evolving beliefs about mathematical competence impacted their STEM identity development. These dichotomies explain the questioning of their mathematical competence and their subsequent decisions to decelerate from the most rigorous program of study at their high school. Our participants negotiated tensions in their STEM identities as a result of a mathematics culture that too often values speed, correctness, and competition over collaboration, productive struggle, and help-seeking. They continue to navigate these tensions as college students and as STEM majors. Our framework can be used to understand how mathematics experiences contribute to students’ struggles to develop robust STEM identities.